2010
DOI: 10.1016/j.yexmp.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of angiocidin with tissue transglutaminase

Abstract: Angiocidin, a matrix bound and tumor associated protein, has been shown to inhibit tumor progression and angiogenesis. We previously demonstrated that angiocidin binds to thrombospondin-1 and alpha2beta1 integrin. We now show that angiocidin binds and is a preferred substrate for tissue transglutaminase-2 (tTgase). Angiocidin bound tissue tTgase saturably with a Kd of 26 nM, while an angiocidin deletion mutant missing the matrix binding domain of angiocidin failed to bind tTgase. tTgase colocalized with angioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…Other TG2-binding proteins, such as PLCδ1 (Hwang et al, 1995; Kang et al, 2002), PKA anchor protein 13 (AKAP13, Lewis et al, 2005), 14-3-3 proteins (Mishra and Murphy, 2006b), Bcr (Yi et al, 2009), and Rac1 (Kim et al, 2010), are localized in the cytoplasm. Additional TG2 interactors include highly abundant ECM proteins such as fibronectin (Turner and Lorand, 1989) or minor ECM components, such as angiocidin (L'Heureux et al, 2010) and endostatin (Faye et al, 2010). On the cell surface, TG2 was found to directly bind matrix metalloproteinase-2 (MMP2; Belkin et al, 2004) and interact with extracellular domains of several transmembrane receptors, including several integrins (Akimov et al, 2000; Zemskov et al, 2006), an atypical orphan GPCR, GPR56 (Xu et al, 2006), syndecan-4 (Telci et al, 2008), platelet-derived growth factor receptor (PDGFR; Zemskov et al, 2009), low density lipoprotein receptor-related proteins 1 (LRP1; Zemskov et al, 2007) and 5/6 (Faverman et al, 2008).…”
Section: Enzymatic and Nonenzymatic Activities Of Tg2mentioning
confidence: 99%
See 1 more Smart Citation
“…Other TG2-binding proteins, such as PLCδ1 (Hwang et al, 1995; Kang et al, 2002), PKA anchor protein 13 (AKAP13, Lewis et al, 2005), 14-3-3 proteins (Mishra and Murphy, 2006b), Bcr (Yi et al, 2009), and Rac1 (Kim et al, 2010), are localized in the cytoplasm. Additional TG2 interactors include highly abundant ECM proteins such as fibronectin (Turner and Lorand, 1989) or minor ECM components, such as angiocidin (L'Heureux et al, 2010) and endostatin (Faye et al, 2010). On the cell surface, TG2 was found to directly bind matrix metalloproteinase-2 (MMP2; Belkin et al, 2004) and interact with extracellular domains of several transmembrane receptors, including several integrins (Akimov et al, 2000; Zemskov et al, 2006), an atypical orphan GPCR, GPR56 (Xu et al, 2006), syndecan-4 (Telci et al, 2008), platelet-derived growth factor receptor (PDGFR; Zemskov et al, 2009), low density lipoprotein receptor-related proteins 1 (LRP1; Zemskov et al, 2007) and 5/6 (Faverman et al, 2008).…”
Section: Enzymatic and Nonenzymatic Activities Of Tg2mentioning
confidence: 99%
“…More recently, angiocidin was found to colocalize with TG2 in the ECM of endothelial cells and to interact noncovalently with TG2 via its C-terminal integrin- and collagen-binding domain (L'Heureux et al, 2010). Intriguingly, the angiocidin–TG2 interaction was found to prevent the deposition of fibronectin in the ECM of tumor and endothelial cells, suggesting that angiocidin-mediated disruption of the TG2–fibronectin interaction is involved in its tumor suppressive activity.…”
Section: Tg2 In Diverse Cellular Compartmentsmentioning
confidence: 99%
“…Angiocidin is an ECM protein expressed by endothelial and tumor cells. Recently, angiocidin was shown to colocalize with TG2 in the ECM of endothelial cells and interact non-covalently with TG2 via its C-terminal integrin and collagen-binding domain [88]. Interaction of angiocidin and TG2 led to inhibition of the TG2-fibronectin interaction as well as inhibition of fibronectin deposition in the ECM of endothelial and tumor cells, which ultimately contributed to modulation of adhesion and migration activities of TG2 [88].…”
Section: Cancer Cell Adhesion Migration and Proliferationmentioning
confidence: 99%
“…Inhibiting angiocidin expression in colon cancer cells and in breast cancer cells have been reported by several groups recently 13,14 . In this study, we indicated for the first time the angiocidin expression in liver cancer cells.…”
Section: Discussionmentioning
confidence: 86%